On the High Performance Liquid Chromatographic Determination and Monitoring of Azadirachtin in Neem Ecotypes - Gupta, P. K.; Prabhu, V. V. (Indian Forester, 1997)
Method was optimised for quantitative determination of azadirachtin content in Neem Seed Kernel (NSK) using High Performance Liquid Chromatographic (HPLC) System. Neem fruits were collected from nine Agro-climatic zones of Rajasthan State and the samples were analysed for the azadirachtin content using this optimised method. The azadirachtin content varied from 0.194% to 0.670% by weight of neem seed kernel.